JUrnal Pengabdian pada Desa PEMANFAATAN SISA ENDAPAN SAMPAH PLASTIK SETELAH PROSES PIROLISIS MENJADI PAVING BLOK SEBAGAI UPAYA PENANGGULANGAN SAMPAH PLASTIK DI DESA LIMBUNG KAB KUBURAYA - Julianto, Eko; Insani, Rachmad Wahid Saleh; Iwan, Muhammad; Gunarto, Gunarto; Sarwono, Eko; Utami, Putri Yuli; Gundiawan, Gundiawan; Setiawan, Agus (Universitas Mataram, 2024)
Dedication has potential in terms of region, physical, social, economic and environmental. Opportunities are still wide open to process plastic waste into other products such as plastic waste as the basic material for making plastic bricks or paving blocks as the main material and the mix of available plastic waste in waste banks is estimated to increase every year. It is hoped that the aim of the service will be a sustainable program and can become a selling point to produce an independent village and can process plastic waste into basic material for paving blocks to support village development as a substitute for sand and cement so that all plastic waste does not end up in piles in waste management and landfills. . The data analyzed is the result of combustion residue on plastic where the plastic deposits after evaporating cannot be used again, therefore we use the plastic deposits in the paving block pressing process. After implementing the treatment, the processing of these plastic paving blocks using a pyrolysis and melting process in a mold mixed with used oil is very effective, where PET is very hard and takes a long time to melt, while LDPE is very easy to decompose and melts when mixed with used oil, whereas HDPE plastic is very easy to use. melted but very fragile in the mold. Where the inside of the paving is still not completely dry and the drying process is quite long. However, this type of PET plastic is very strong, sturdy and heavy. This is because the related tests have not been carried out to test the hardness of paving and materials as well as testing during floods where this paving is relatively lighter than cement paving on the market. Therefore, it is necessary to carry out chemical tests for paving mixed with PET LDPE and HDPE. In this case the Service only carries out treatment of plastic which has been a waste problem until now for special development and infrastructure needs by utilizing non-organic waste.